2006
DOI: 10.1017/s0952523806231043
|View full text |Cite
|
Sign up to set email alerts
|

Natural images and contrast encoding in bipolar cells in the retina of the land- and aquatic-phase tiger salamander

Abstract: Intracellular recordings were obtained from 57 cone-driven bipolar cells in the light-adapted retina of the land-phase (adult) tiger salamander (Ambystoma tigrinum). Responses to flashes of negative and positive contrast for centered spots of optimum spatial dimensions were analyzed as a function of contrast magnitude. On average, the contrast/response curves of depolarizing and hyperpolarizing bipolar cells in the land-phase animals were remarkably similar to those of aquatic-phase animals. Thus, the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 26 publications
6
34
0
Order By: Relevance
“…Thus, the fraction of dark contrasts exceeded the fraction of bright contrasts even without divisive normalization. These findings extend early reports of specific instances of a skew to negative contrasts (15,28,29).…”
supporting
confidence: 90%
“…Thus, the fraction of dark contrasts exceeded the fraction of bright contrasts even without divisive normalization. These findings extend early reports of specific instances of a skew to negative contrasts (15,28,29).…”
supporting
confidence: 90%
“…This evidence for matched amplification provides a new view for the function of light adaptation and the contribution of the cone-bipolar synapse in vertebrate vision. Work to date suggests that our results for contrast flashes also apply to image movement on the retina (Burkhardt et al, 2006).…”
Section: Distributed Coding In Bipolar Cells and Natural Imagesmentioning
confidence: 61%
“…Although the retina of the aquatic-phase salamander has been studied extensively for some four decades by many investigators, no reports were known for land-phase animals. We found, on average, that the contrast-response curves of ON and OFF bipolar cells in the landphase animals were remarkably similar to those of aquatic-phase animals (Burkhardt et al, 2006). Thus, the primary retinal mechanisms mediating contrast coding in the outer retina remain functionally stable as the salamander evolves from the aquatic to the land phase.…”
Section: Distributed Coding In Bipolar Cells and Natural Imagesmentioning
confidence: 69%
See 1 more Smart Citation
“…Ganglion cells with response properties similar to those of the fast-OFF cells studied in our larval salamanders have also been explored in a variety of other amphibians and mammals (Lettvin et al, 1959;Shapley and Victor, 1978;Berry et al, 1999;Petrusca et al, 2007), and are presumably found in both the larval and adult form of the tiger salamander. Indeed, contrast coding in the outer retina of larval tiger salamanders has been shown to be functionally equivalent to that in terrestrial adults (Burkhardt et al, 2006). For these reasons, we believe that the larval tiger salamander is both a representative and experimentally accessible system in which to begin studying the motion processing experienced by both aquatic and terrestrial amphibians.…”
Section: Methodsmentioning
confidence: 96%